Processos de educar-se de mulheres do assentamento Monte Alegre – SP nas ações de cuidado à saúde - Teixeira, Iraí Maria de Campos (2016)
The access to a well sorted healthcare system – one that provides services and medical and multidisciplinary care – by rural populations is poor. Difficulties in accessing these services strengthen the exclusion of the peasant. In addition, farming can expose families to environmental, ergonomic and incidental risks, putting their health in danger. These findings can be used to ponder the failures involving healthcare programs for rural populations. Caring involves respect for beliefs, values, the feelings of others and also the feelings of oneself, enhancing one’s interior space. Care is existential, relational, contextual and complex, built by beings that take and receive care. Healthcare is understood here as any action intended to promote, maintain or restore health. It includes health as a dynamic factor in life, always singular, founded on the ceaseless activity of being alive and corresponding to the ability to face adversity and to expand living conditions. In this study, healthcare is taken as a social practice that manifests the cultural peculiarities of those who practice it and generates interactions between individuals and the natural, social and cultural environments in which they live in. In social practices, some educational processes understood as relationships in which individuals give meaning to each other and the world they acquire their experiences, are promoted. Actions and relationships are developed within the social practices in order to secure the material and symbolic survival of groups and also solve problems they face. This study aims at investigating the educational processes on healthcare developed by women from a settlement located in the central area of the state of São Paulo. Both activities and reflections involved in the ongoing process of praxis and building of knowledge in health are considered healthcare. The methodology used is the Participative Research, with coexistence and dialogue as methodological principles. Participant observations and semi-structured interviews were conducted. By the analysis of the collected data the following analytical categories were seized: 1) Joint actions and collective work; 2) Living together, cohabiting and sharing; 3) Intergenerational relations; 4) Home acquaintanceship; 5) Going public; and 6) The space of popular healthcare practices. It is shown the importance of learning from the peasant women whose healthcare practices contribute to overcoming inequalities and challenges imposed to them and maintain their material and symbolic survival and an effective healthcare promotion to rural populations. This work aims at strengthening health care actions performed by these women from a dialogical process of research building, expecting that hopefully it will bring more visibility to their actions in academic, political and social means.